Peran Komunikasi Dalam Mengelola Manajemen Stress (Studi Kasus: Universitas Budi Darma) - Anda Yanny; Ronda Deli Sianturi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The Covid-19 virus that entered Indonesia, especially the city of Medan, forced the government to cancel face-to-face learning activities and replace them with online learning. This makes some students have difficulty understanding the learning provided by the lecturer online, as well as the eighth semester who carries out online thesis guidance using several learning applications. This difficulty brings students to stress, besides they do not understand the lecturer's instructions plus pressure from their families who force them to finish their thesis as soon as possible. Communication is the solution to this problem. Good form and communication will reduce the impact of stress on students and can motivate them to go through the implementation of the thesis without heavy stress